Dampak Kemajuan Teknologi Informasi dan Komunikasi terhadap Nilai-Nilai Budaya - Rizky Febriansyah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study examines the impact of advancements in Information and Communication Technology (ICT) on cultural values, focusing on changes and the preservation of local cultures. The method used is descriptive analysis based on interviews, observations, and document studies. The results reveal that ICT has significantly influenced local cultural values, including shifts in cultural identity among younger generations, increasing individualism, and cultural homogenization due to social media. On the other hand, ICT offers opportunities for cultural preservation through digitalization and the promotion of local cultures on digital platforms. Nonetheless, challenges persist in maintaining traditional cultural values rooted in collectivism, given the dominant influence of global culture. This study recommends the need for prudent strategies in utilizing ICT to preserve local cultures without compromising their cultural identity.